1999
DOI: 10.1038/6529
|View full text |Cite
|
Sign up to set email alerts
|

Transplantability and therapeutic effects of bone marrow-derived mesenchymal cells in children with osteogenesis imperfecta

Abstract: In principle, transplantation of mesenchymal progenitor cells would attenuate or possibly correct genetic disorders of bone, cartilage and muscle, but clinical support for this concept is lacking. Here we describe the initial results of allogeneic bone marrow transplantation in three children with osteogenesis imperfecta, a genetic disorder in which osteoblasts produce defective type I collagen, leading to osteopenia, multiple fractures, severe bony deformities and considerably shortened stature. Three months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
1,162
2
28

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 1,673 publications
(1,209 citation statements)
references
References 26 publications
(32 reference statements)
17
1,162
2
28
Order By: Relevance
“…Therefore, bone marrow transplantation has been undertaken in patients with genetic bone diseases, for example osteogenesis imperfecta and may have a therapeutic effect in osteogenesis imperfecta. 21,22 In hypophosphatasia, allogeneic bone marrow and/or MSC transplantation therapy has been reported by us and other groups. 4,14,23 However, the disease was not curable with these allo-transplantation therapies.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, bone marrow transplantation has been undertaken in patients with genetic bone diseases, for example osteogenesis imperfecta and may have a therapeutic effect in osteogenesis imperfecta. 21,22 In hypophosphatasia, allogeneic bone marrow and/or MSC transplantation therapy has been reported by us and other groups. 4,14,23 However, the disease was not curable with these allo-transplantation therapies.…”
Section: Discussionmentioning
confidence: 89%
“…The safety of autologous and allogeneic MSC products has been established in these trials and no toxicity was documented. Due to the ability of MSCs to differentiate into osteocytes, they have been used as adjunct therapy to marrow transplantation in osteogenesis imperfecta (Horwitz et al, 1999(Horwitz et al, , 2002. The rationale was to introduce cells with a healthy gene that produce physiologic bone matrix.…”
Section: Mscmentioning
confidence: 99%
“…Three of the children who received bone marrow transplantation were documented to exhibit donor osteoblasts in their bones 3 months after cell transplantation. 44 The children who were shown to possess osteoblast engraftment after 6 months of marrow infusion were reported to exhibit an increase in body length. The patients also gained 45-77% of total bone mineral content from the baseline values and also exhibited a reduction in fracture rates.…”
Section: Analysis Of the Ceramic Cubes At Different Time Pointsmentioning
confidence: 99%
“…The authors concluded that bone marrow transplantation from normal donors to OI patients might be of benefit in OI. [44][45][46] The number of donor cells that engrafted in marrow recipients was however very small. At 3 months after bone marrow transplantation, only 1.5-2% of the cells in trabecular bone of the cell recipients were estimated to be of the donor origin.…”
Section: Analysis Of the Ceramic Cubes At Different Time Pointsmentioning
confidence: 99%